2021
DOI: 10.1186/s12877-021-02182-1
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of geriatric-quickSOFA in hospitalized older people with sepsis

Abstract: Background QuickSOFA, a prognostic score proposed for patients with infection, has shown a poor predictive value in the geriatric population, probably because of the inappropriateness of the Glasgow Coma Scale (GCS) in assessing acute alteration of mental status in older patients. Indeed, the GCS might result chronically low in older patient with pre-existing cognitive disorders. The aim of this study was to develop an alternative quickSOFA (geriatric-quickSOFA), using the presence of delirium,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…The current study demonstrated the different predictive performance of the qSOFA score for in-hospital mortality between young and elderly OAPN patients; the qSOFA score predicted in-hospital mortality with high accuracy in young patients (AUC, 0.85), whereas its prognostic accuracy was modest in elderly patients (AUC, 0.61). This trend was also observed in several previous studies, in which the AUC of the qSOFA score was less than 0.70 in elderly patients [ 17 , 18 , 19 ]. The sensitivity and specificity of qSOFA score ≥ 2 for in-hospital mortality were 80% and 80% in young patients, and 50% and 68% in elderly patients, respectively.…”
Section: Discussionsupporting
confidence: 88%
“…The current study demonstrated the different predictive performance of the qSOFA score for in-hospital mortality between young and elderly OAPN patients; the qSOFA score predicted in-hospital mortality with high accuracy in young patients (AUC, 0.85), whereas its prognostic accuracy was modest in elderly patients (AUC, 0.61). This trend was also observed in several previous studies, in which the AUC of the qSOFA score was less than 0.70 in elderly patients [ 17 , 18 , 19 ]. The sensitivity and specificity of qSOFA score ≥ 2 for in-hospital mortality were 80% and 80% in young patients, and 50% and 68% in elderly patients, respectively.…”
Section: Discussionsupporting
confidence: 88%
“…Sepsis has become one of the main causes of death in the geriatric population. 16 Elderly patients with sepsis account for 58-65% of all patients with sepsis. [17][18][19] Studies have shown that the incidence and mortality of sepsis increase with age.…”
Section: Discussionmentioning
confidence: 99%
“…21 The qSOFA lacks effectiveness in predicting sepsis mortality among hospitalized patients. 14,26,27 Remelli et al identified a geriatric-quick SOFA incorporating clinical parameters and delirium. 26 Their multivariable logistic regression, including age, male gender, basic and instrumental ADL, and bedridden status, showed increased odds ratios for in-hospital and 30-day mortality.…”
Section: Resultsmentioning
confidence: 99%
“…14,26,27 Remelli et al identified a geriatric-quick SOFA incorporating clinical parameters and delirium. 26 Their multivariable logistic regression, including age, male gender, basic and instrumental ADL, and bedridden status, showed increased odds ratios for in-hospital and 30-day mortality. Similarly, our study revealed concurrent risk factors for patient dependence (at least one independent basic ADL) and altered mental status.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation